ANALISIS PENGARUH BAURAN PEMASARAN 7P TERHADAP KEPUASAN PELANGGAN PENGGUNA GOJEK ONLINE - Farida, Ida; Tarmizi, Achmad; November, Yogi (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2016)
The purpose of this study is to examine the impact of seven elements of marketing mix (product, price, place, promotion, people, process and physical evidence) on customer satisfaction of GOJEK users. Data were collected from 90 customers residing in South Jakarta using self-reporting questionnaires. Factor analysis is used to validate the instrument and regression analysis was used to test the hypotheses. The results showed that although the elements of the marketing mix simultaneously significant effect on customer satisfaction, however partially, only the product have a significant effect on customer satisfaction (p-value 0.045). Based on these findings, the future research needs to re-examine the influence of marketing mix elements on customer satisfaction, in particular, transport mode users GOJEK by increasing the sample size and expanding the area of research so that research results can be generalized. Keywords: Product, Price, Promotion, Place, Process, People, Physical Evidence, Satisfaction